Chemical characterization and water content determination of bio-oils obtained from various biomass species using 31P NMR spectroscopy. Issue 2 (March 2012) - David, Kasi; Ben, Haoxi; Muzzy, John; Feik, Calvin; Iisa, Kristiina; Ragauskas, Arthur
Background: Pyrolysis is a promising approach to utilize biomass for biofuels. One of the key challenges for this conversion is how to analyze complicated components in the pyrolysis oils. Water contents of pyrolysis oils are normally analyzed by Karl Fischer titration. The use of 2-chloro-4, 4, 5, 5, -tetramethyl-1, 3, 2-dioxaphospholane followed by 31 P NMR analysis has been used to quantitatively analyze the structure of hydroxyl groups in lignin and whole biomass.Results: 31 P NMR analysis of pyrolysis oils is a novel technique to simultaneously characterize components and analyze water contents in pyrolysis oils produced from various biomasses. The water contents of various pyrolysis oils range from 16 to 40 wt%. The pyrolysis oils obtained from Loblolly pine had higher guaiacyl content, while that from oak had a higher syringyl content.Conclusion: The comparison with Karl Fischer titration shows that 31 P NMR could also reliably be used to measure the water content of pyrolysis oils. Simultaneously with analysis of water content, quantitative characterization of hydroxyl groups, including aliphatic, C-5 substituted/syringyl, guaiacyl, p -hydroxyl phenyl and carboxylic hydroxyl groups, could also be provided by 31 P NMR analysis.